PERBEDAAN EFEKTIVITAS ANESTETIKUM ANTARA ZOLETILACEPROMACIN DAN KETAMIN- ACEPROMACIN PADA TIKUS PUTIH (Rattus norvegicus) - Retina Yunani; Era Hari Mudji; Desty Apritya (JURNAL KAJIAN VETERINER, 2019)
The aim of this research was to find out the effects of zoletil–acepromacin and ketamin–acepromacin as general anaesthetics on heartbeat, respiratory rate, bodytemperature, onset of action and duration of action in rat. This research used much as 27 rats and were divided into 3 group of treatments. P0 as a control group was injected with aquabidest by intraperitoneal injection. P1 was injected with atropine sulphate (0,05mg.kg BW) SC for premedication and ketamin (75mg/kgBW) - acepromacin (2,5 mg/kg BW) by IP as anaesthetic. P2 was injected with atropine sulphate (0,05mg/kg BW) SC for premedication and zoletil (50mg/kgBW) - acepromacin (2,5 mg/kg BW) by intraperitoneal as anesthetic. The results showed that the combination of Ketamin-Acepromacin and Zoletil-Acepromacin depress the heart beat and respiratory rate. The body temperature in P2 were recorded lower than in P1. However, the onset of action and duration were longer in P1 than in P2.